Knowledge management system for vegetables farmers in Pahang - Nur Iffatul Hanisa, Mohamad Rozulan (2012)
The project is about the system for Pahang Agriculture Department.This system is applying knowledge management technique to manage the data information.This system is developed to help farmers in managing their knowledge.The methodology that had been applied to develop this system is iterative and incremental methodology.This study found that the farmers can share their knowledge even the farmers already retire.This mean,the knowledge from experts can be shared to everyone.The iterative and incremental methodology is flexible and easy to manage more manageable process and better software making and better software structure.This system is available to farmers and all users around the world.By using this system is to make the knowledge about agriculture continuous even the farmers are retired.The farmers also can introduce their product to anyone in the world.Hence,for the farmers that not retired yet,they also can improve their business and also share their experiences and knowledge.